Stress Distributions in an Elastic Semi-space Due to Point Sources - Gozde, S.; Chowdhury, L. (Engineering Transactions, 1984)
Exact closed form expressions for the displacements and stresses are constructed for a linear isotropic elastic semi-space subjected to point sources applied at a finite distance h beneath its stress-free piane boundary. Point-sources considered are a single force, a double-force, a centre of rotation and a centre of dilatation. Equations of elasto-statics are solved using the potential function approach of PAPKOVITCH and NEUBER [5], and explicit expressions for potentials are generated when the above forces are placed in an infinite-space. Expressions for the half-space potentials are developed from the full-space potentials by Aderogba's integro-differentia formulae. Three-dimensional graphs depict variation of stresses in the interior of the elastic semi-space.